Etos Itqān dalam Hadis Nabi SAW sebagai Fondasi Pendidikan Karakter di Era Artificial Intelligence (AI) - Mohammad Kurnaini; Amelia Damayanti; Muhammad Yusriel Amien; Muhammad Rizqy Putra Sentosa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This addresses the rapid advancement of Artificial Intelligence (AI) in education, which presents both opportunities and challenges for character building, particularly regarding work ethic, responsibility, and academic integrity. The use of AI without ethical awareness has the potential to reduce the quality of the thinking process and the meaning of learning. Therefore, a value framework is needed that can guide the responsible use of technology. This research aims to examine the concept of itqān in the hadith of the Prophet Muhammad (peace be upon him) as the foundation of work ethics and analyze its relevance in education in the AI ​​era. The formulation of the concept of itqān in this research is not only an individual work ethic, but as an operational pedagogical ethical principle in guiding the use of AI in the learning process. This research uses a qualitative approach with a type of library research, through content analysis of the hadith of the Prophet and literature related to character education and artificial intelligence. The results show that itqān is an ethical principle rooted in the values ​​of iḥsān, amanah, ikhlāṣ, and mas’ūliyyah which emphasizes sincerity, thoroughness, and responsibility in every deed. In the context of AI, itqān serves as a normative framework that guides the critical and verifiable use of technology, without replacing human thought processes. Therefore, integrating itqān values ​​into education can strengthen students' character, ensuring they remain oriented toward process quality and integrity amidst technological advancements. This research contributes conceptually to formulating an Islamic-based pedagogical ethic that is adaptive to the development of AI.